Status, Breeding Ecology and Conservation of the Imperial Eagle in Austria - Matthias Schmidt; Johannes A. Hohenegger (Пернатые хищники и их охрана)
The Imperial Eagle (Aquila heliaca, IE) reaches the western limit of its global breeding in range in Austria. As a result of targeted conservations measures in the Pannonian region, namely Hungary and Slovakia, the species repopulated Austria in 1999, nearly 190 years after its extirpation. Since then, a strong population increase took place and was monitored closely through different species conservation programmes of BirdLife Austria. Apart from the population monitoring, the programmes comprised measures to prevent illegal persecution and the disturbance of breeding sites, the satellite tagging of young IEs and the collection of all mortality data available.